Teaching international public relations: an interactive approach - Sharpe, Melvin L.; Simões, Roberto Porto; Steffen, Ana Roig (Revista FAMECOS, 2008)
Ball State University in Muncie, Indiana, and the Pontifical Catholic University of Rio Grande do Sul in Porto Alegre, Brazil, have joined public relations campaigns classes to teach students the lessons that need to be learned in international public relations performance. Class assignments include research to build knowledge of culture, government, and the media within each others countries. Student campaign teams must use each other as counselors in learning about differences in culture and public relations performance needs. They must also conduct research instructing and using each other in carrying out research activities in the same working relationship that they must eventually use as professionals in carrying out campaigns in each other’s countries.